2012
DOI: 10.1182/blood-2012-02-410241
|View full text |Cite
|
Sign up to set email alerts
|

Notch is active in Langerhans cell histiocytosis and confers pathognomonic features on dendritic cells

Abstract: Langerhans cell histiocytosis (LCH) is an enigmatic disease defined by the accumulation of Langerhans cell-like dendritic cells (DCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 49 publications
(68 reference statements)
5
94
0
5
Order By: Relevance
“…In the present study, we indeed demonstrated that E-cadherin expression was readily induced on MDLCs when cocultured with primary KCs and that this was partly due to the Notch signaling pathway activation as suggested by the DAPT blockade (28). Moreover, we provided further evidence that E-cadherin-dependent interactions between MDLCs and KCs were crucial to generate fully differentiated MDLCs as reported by others in two-dimensional cultures (45,58). Noticeably, to our knowledge, DLL1 does not exist as a clinical-grade reagent whereas GM-CSF, TGF-b1, and human albumin do, thus precluding the development of preclinical or clinical applications involving human LC-like cells using the DLL1 approach reported by Hoshino et al (28).…”
Section: Discussionsupporting
confidence: 66%
“…In the present study, we indeed demonstrated that E-cadherin expression was readily induced on MDLCs when cocultured with primary KCs and that this was partly due to the Notch signaling pathway activation as suggested by the DAPT blockade (28). Moreover, we provided further evidence that E-cadherin-dependent interactions between MDLCs and KCs were crucial to generate fully differentiated MDLCs as reported by others in two-dimensional cultures (45,58). Noticeably, to our knowledge, DLL1 does not exist as a clinical-grade reagent whereas GM-CSF, TGF-b1, and human albumin do, thus precluding the development of preclinical or clinical applications involving human LC-like cells using the DLL1 approach reported by Hoshino et al (28).…”
Section: Discussionsupporting
confidence: 66%
“…36,37 Intrinsic notch signaling was previously suggested as a key mechanism promoting LCH pathogenesis, through expression of Jagged 2 by lesional histiocytes. 28 Taken together, these observations do not support a simple dichotomous model that LCH arises from the DC pathway and ECD from the monocyte-macrophage pathway of myeloid cell development. Classical monocytes appear able to contribute to histiocytes of both disorders, depending on the signals they receive.…”
Section: V600ementioning
confidence: 69%
“…Various metalloproteinases have been identified in LCH granulomas and could account for LCH-induced tissue destruction [49,50,60]. Recently, the activation of the Notch1 signalling pathway has been shown to be at least partly responsible for the specific profile of LCH cells [49].…”
Section: Pathogenesismentioning
confidence: 99%
“…The cell-specific gene expression signature in Langerin (CD207) + cells within LCH lesions has shown that these cells are more consistent with immature myeloid dendritic cell precursors than Langerhans cells [49,50].…”
Section: Pathogenesismentioning
confidence: 99%